Three essays on personal financial difficulties of military members - Nelson, Jeffrey S. (Kansas State University, 2014)
This three essay dissertation examined questions related to personal financial difficulties of military members with the aim of suggesting the most effective focal points for those involved in development of policy or programs or working directly with military members on improving their personal financial condition. The introduction (Chapter 1) describes the nature of the problem, the level of attention it has received within the civilian and military leadership structure, and generally what has been done to address it before presenting an outline of the chapters which follow. The first essay (Chapter 2) relies on theoretical guidance from stress and coping theory to examine determinants of a military member’s choice of problem-focused over emotion-focused coping strategies. The study used primary data collected from a sample of soldiers (n = 688) at a large Midwestern military installation. Its results indicated that military members with an internal locus of control and those who performed positive financial behaviors in response to a financial stressor reported lower levels of financial stress. Taking its theoretical guidance from the theory of planned behavior, the second essay (Chapter 3) examined the relationship of the behavioral antecedents of attitude toward behavior, subjective beliefs, and perceived behavioral control with behaviors related to establishing and maintaining an adequate emergency fund and maintaining positive cash flow, the term used for keeping spending at levels below income over time. The study analyzed primary data from a sample of soldiers at a large Midwestern military installation (n = 93). Of the 11 models analyzed, most were statistically significant, though, individually, the behavioral antecedents themselves did not yield statistical significance as often. Although fewer definitive findings emerged from the cash flow group of models, results of the emergency fund group indicated that attitude toward behavior and perceived behavioral control are positively influential on behaviors related to maintaining an emergency fund. The third essay (Chapter 4) detailed a study which tested the theoretical assumption that better informed consumers make better financial choices. The study examined self-assessed financial knowledge, a self-assessed measure of confidence in day-to-day personal financial management termed financial confidence, and objectively measured financial knowledge as potential determinants of certain positive and negative financial behaviors. The positive behaviors were maintenance of positive cash flow and an adequate emergency fund, and the negative behaviors were engaging in high-cost borrowing through auto title lenders, payday lenders, pawn shops, and rent-to-own stores, collectively termed alternative financial services (AFS). The study analyzed secondary data from a sample of military members collected by the 2012 National Financial Capability Study which yielded a set of 949 responses useable for the study described in this chapter. Subjective knowledge was found to be associated with emergency fund maintenance, but not positive cash flow, while objective financial knowledge and financial confidence were found to be positively associated with positive cash flow, but not emergency fund maintenance. Females and those with higher incomes were found to be more likely to maintain positive cash flow, while those with three or more dependent children and those having experienced a recent income shock were less likely to do so. Females, members with graduate degrees, and members with a higher investing risk tolerance were more likely to maintain emergency funds, though members with two or more children and those having experienced a recent income shock were less likely to do so. Subjective financial knowledge was found to be positively related to AFS use, while objective financial knowledge and financial confidence were found to be negatively associated with AFS use. Members with more dependent children and those having experienced recent income shocks were more likely to have used AFS, while those with higher incomes were less likely to have done so. The conclusion (Chapter 5) summarizes the findings of all three essays, their implications, and suggests directions for future research. It re-emphasizes the unique contributions of the essays to personal finance literature pertaining to military members and its importance for policy makers, military leaders, and anyone involved in developing or administering personal financial improvement programs for the benefit of military members.
Keywords: Personal finance; Military; Financial stress; Individual & Family Studies (0628)